Smart wheel chair - Sarmad Hameed; Muhammad Hamza Shoukat; Abdur Rafay Khan; Khwaja Mobeen Haroon (Annals of Robotics and Automation - Peertechz Publications, 2021)
While degrading mobility, one of the major concerns affecting the independent ability of elderly / disabled people to live. Mobility assistive technologies are now being built to uplift people's living conditions. However, improvements are required to existing mobility assistive devices. This paper explores designing and building a smart wheel chair with several control interfaces. A version of the smart wheelchair device was built based on a currently accessible traditional wheelchair on the market, with the introduction of similar electrical and mechanical developments. To improve user involvement, the system includes speech and gesture-control interfaces as addition to the Mobile Application for controlling the Wheel Chair. Particulars are presented regarding the mechanical design, the smart wheelchair's electrical and control system. Experiments were carried out to verify the functionality of the smart wheelchair that was developed. Furthermore addition, a user study evaluated the user preferences between the different controlling interfaces, and the results are presented.